2021
DOI: 10.3390/antiox10091493
|View full text |Cite
|
Sign up to set email alerts
|

Lycopene Protects Intestinal Epithelium from Deoxynivalenol-Induced Oxidative Damage via Regulating Keap1/Nrf2 Signaling

Abstract: Deoxynivalenol (DON) is a threatening mycotoxin primarily present in the agricultural environment, especially in food commodities and animal forages, and exerts significant global health hazards. Lycopene (LYC) is a potent antioxidant carotenoid mainly present in tomatoes and other fruits with enormous health benefits. The present study was designed to ascertain whether LYC could protect DON-induced intestinal epithelium oxidative injury by regulating Keap1/Nrf2 signaling in the intestine of mice. A total of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 51 publications
1
21
0
Order By: Relevance
“…The higher expression of GSTr in muscle might lead to the more sensitive response to VA; however, this needs further characterization. In mammal, the expression of antioxidative enzymes genes (such as CAT and CuZnSOD ) can be modulated by Nrf2 signaling [ 43 ]. The present study observed that dietary VA deficiency decreased mRNA levels of Nrf2 , protein levels of total Nrf2, and nuclear Nrf2, while enhancing the mRNA levels of Keap1a in grass carp muscle.…”
Section: Discussionmentioning
confidence: 99%
“…The higher expression of GSTr in muscle might lead to the more sensitive response to VA; however, this needs further characterization. In mammal, the expression of antioxidative enzymes genes (such as CAT and CuZnSOD ) can be modulated by Nrf2 signaling [ 43 ]. The present study observed that dietary VA deficiency decreased mRNA levels of Nrf2 , protein levels of total Nrf2, and nuclear Nrf2, while enhancing the mRNA levels of Keap1a in grass carp muscle.…”
Section: Discussionmentioning
confidence: 99%
“…38 However, LYC alleviated DON-induced oxidative stress by reducing ROS and MDA accumulation and enhancing the activity of antioxidant enzymes (SOD and GSH-Px) and T-AOC, which are linked to the activation of NRF2 signaling and a decline in KEAP1 expression. 39 Our results showed that co-exposure to ZEN, DON, and AFB1 caused oxidative damage (reduced T-AOC level and increased MDA and ROS contents) in the jejunum of mice. The protective effects of LYC against ZEN + DON + AFB1-induced oxidative damage have been demonstrated in this study.…”
Section: Papermentioning
confidence: 52%
“…Furthermore, the depth of the crypts in the small intestine of the mice was increased. Studies have shown that DON exposure caused oxidative stress in the intestine, including changes in the mRNA expressions of CAT, GSH-PX, and the serum MDA content, which led to a cascade of intestinal damage. , HO-1 is a well-known antioxidant factor, and several studies have shown that HO-1 plays an anti-inflammatory and antioxidant role, protecting the body from external damage. In the present study, the protein and mRNA levels of HO-1 were found to decrease significantly in the DON-exposed group, which is consistent with previous studies. , Likewise, DON exposure reduced the mRNA levels of CAT and SOD-2 in mouse jejunum. In vitro, the results showed that 0.5–2 μM DON significantly reduced the protein and mRNA expressions of HO-1 and increased ROS generation.…”
Section: Discussionmentioning
confidence: 76%
“…29−31 In the present study, the protein and mRNA levels of HO-1 were found to decrease significantly in the DON-exposed group, which is consistent with previous studies. 11,32 Likewise, DON exposure reduced the mRNA levels of CAT and SOD-2 in mouse jejunum. In vitro, the results showed that 0.5−2 μM DON significantly reduced the protein and mRNA expressions of HO-1 and increased ROS generation.…”
Section: Discussionmentioning
confidence: 93%